Cytotoxic and Apoptotic-inducing Effect of Fraction Containing Brazilein from Caesalpinia sappan L. and Cisplatin on T47D Cell Lines - Prisnu Tirtanirmala; Annisa Novarina; Rohmad Yudi Utomo; Raisatun Nisa Sugiyanto; Riris Istighfari Jenie; Edy Meiyanto (Indonesian Journal of Cancer Chemoprevention, 2015)
Anticancer activity of secang’s heartwood (Caesalpinia sappan L.) is based on its main compound: brazilin and brazilein. Brazilin, brazilein, and other compounds such as caesalpiniaphenol can affect proteins that have a role in apoptosis. In this study, we observed cytotoxic activity of fraction containing brazilein (FCB) alone or in combination with chemotherapeutic agent, cisplatin and the ability of the combination to induce apoptosis in T47D breast cancer cell lines. Cytotoxicity assay was determined using MTT assay, whereas the detection apoptosis induction was conducted using flow cytometry using Annexin-V and propidium iodide. FCB and cisplatin showed cytotoxic effect on T47D cells with IC50 value of 68 µg/mL and 16 µM, respectively. Combination of FCB and cisplatin result synergistic combination at the concentration ratio of 1/2 IC50 with CI value of 0.66. Its combination also able to induce apoptosis on T47D cell population 13% larger than the single treatment. Based on this study, we conclude that FCB is able to enhance the cytotoxic effects of cisplatin by inducing apoptosis.Keywords:  Caesalpinia sappan L., cisplatin, apoptosis, breast cancer